Optimizing the Na metal/solid electrolyte interface through a grain boundary design. Issue 10 (14th February 2022) - Wang, Chengzhi; Sun, Chen; Sun, Zheng; Wang, Boyu; Song, Tinglu; Zhao, Yongjie; Li, Jingbo; Jin, Haibo
Abstract : We propose grain boundary sealed Na3 Zr2 Si2 PO12 (GBS-NZSP) to address the critical issues of solid-state Na batteries. Ultra-stable Na plating/striping cycles and high-rate solid-state Na metal batteries are realized at room temperature. Abstract : Poor compatibility between an alkaline metal electrode and solid electrolyte at interfaces is the critical issue for solid-state metal batteries. We propose a grain boundary sealing (GBS) design of the Na3 Zr2 Si2 PO12 (denoted as GBS-NZSP) solid electrolyte to enhance interfacial contact with Na metal and realize stable Na plating/stripping cycles at room temperature. (ZnO)2 –(B2 O3 )3 (ZBO) is selected to promote densification sintering of NZSP and seal the grain boundary from electrons, thus suppressing Na metal dendrite growth and maintaining interfacial stability during charge/discharge cycles. The optimal GBS-NZSP reaches an impressive interfacial resistance of 23 Ω cm 2, over 41 times lower than that of bare NZSP against Na metal at 25 °C. The corresponding symmetrical Na//Na cell preserves super cycling stability for 1400 h at 0.3 mA cm −2 . The excellence is attributed to the positive effect of the GBS design on enhanced ionic conductivity and reduced electron transfer at the grain boundary, which leads to steady high-flux Na + -ion migration across the solid electrolyte without dendrite formation. Moreover, a 4 V full cell of Na3 V1.5 Cr0.5 (PO4 )3 /GBS-NZSP/Na is assembled accordingly, exhibiting high-rate capability and delivering a capacity of 108 mA h g −1 for 560 cycles with over 80% retention at 10C rate.